Tingkat Kecemasan dan Harga Diri Remaja Terhadap Kesehatan Mental di SMAN 7 Bengkulu Selatan - Elnita V, Lestin; Saputra, Zolan; Susanti, Jeni (Yayasan Darussalam Bengkulu, 2023)
This study aims to examine the influence of adolescents' levels of anxiety and self-esteem on mental health at SMAN 7 South Bengkulu. This research uses quantitative methods, the data collection technique is by distributing a question-naire of 30 items. The sample studied was teenagers from SMAN 7 South Bengkulu. Data were collected from 103 respondents. This research was ana-lyzed using quantitative analysis using SPSS by testing correlation regression, normality test, reliability test and R Square. Based on the results of this study, it shows the influence of teenagers' anxiety levels and self-esteem on mental health at SMAN 7 South Bengkulu is in the weak category, namely 07.1%.